Participatory technology application and multi-stakeholder convergence for market-led agripreneurship and sustainable rural livelihood - Burman, R Roy; Padaria, R N; Sharma, Shailendra; Singh, Rahul; Tomer, B S; Chahal, V P; Singh, A K (Indian Farming, 2022)
.